Assessment of olfactory fossa depth using computed tomography imaging in a tertiary care setting - Shantala Sawkar; Adarsh AD; Anil Kumar Sakalecha; Mahima Kale R; Soumya Z Chincholikar (Asian Journal of Medical Sciences, 2024)
Background: Chronic sinonasal disorders are commonly treated surgically with endoscopic sinus surgery. Keros classifies the olfactory fossa (OF) into three groups according to the ethmoid roof level. The depth of the OF is determined by the size of the lateral lamella of the cribriform plate. Multidetector computed tomography is gold standard in evaluating the structure of the nasal cavity and paranasal sinuses (PNS). Aims and Objectives: The aim of the study was to examine non-enhanced computed tomography (CT) scans of the paranasal sinus and analyze the depth of the OF to identify and categorize different Keros types and to evaluate anatomical variances to prevent major surgical complications. Materials and Methods: IM was a prospective study and 160 patients were enrolled for the study. The study was undertaken in the Department of Radiodiagnosis at Sri Devaraj Urs Medical College in Tamaka, Kolar. Patient with chronic sinonasal disorders undergoing pre-operative non-enhanced CT PNS study was enrolled in the study. The depth of the OF was measured and categorized into three groups according to Keros classification. Results: Out of 160 participants, 115 (71.8%) were male. The depth of the OF on the right (P=0.28) or left (P=0.66) did not differ significantly between genders. In men, the most prevalent (n=92, 57.5%) was Type-II Keros on the right, with 80 (50%) patients on the left. Type-1 Keros was more common in females on the right side (18 patients, 11.2%), whereas Type-II Keros was more common on the left side (20 patients, 12.5%). The proportion of different types of Keros differed significantly across genders (P<0.001). Conclusion: This study reveals that Keros Type-II was the most prevalent among participants. Comprehensive insights into the anatomical variability of the olfactory region are pivotal for through pre-operative assessment of patients with nasal and PNS disorders in preventing significant surgical complications.